REDESIGNING COMPETENCY-BASED ESP CURRICULUM FOR AEC: A CASE STUDY OF ENGLISH FOR BUSINESS COMMUNICATION - Amporn Sa-ngiamwibool (University of Muhammadiyah Purwokerto, 2013)
Thailand has undergone continuing changes which affect all areas of education, including ESP education. To cope with all the changes including AEC in 2015, the ESP curriculum needs to be redesigned. This study was therefore to explore the perceptions and attitudes towards the redesigned English Business Communication. This study was based on triangulation. The instruments included an interview and a questionnaire. The subjects were 5 key informants whose main areas of expertise were ESP education, 70 graduates and students of English for Business Communication and 10 entrepreneurs. The informants were interviewed to elicit data for SWOT analysis while the graduates, the students and the entrepreneurs were surveyed through a questionnaire to elicit the data on the curriculum based on competency-based and holistic language learning. The SWOT analysis indicated that the redesigned curriculum should direct towards competence regarding to a combination of contents, skills and professional attitudes needed for effective communication and performance, a preparation for increased competition and changes, a response to internationalization, a shift from generalization to adaptive specialization, and sustainable quality orientation. The survey revealed that the respondents agreed that the curriculum could help prepare for AEC. The implication indicated that the ESP curriculum for changes should direct towards competency and the findings of this study will help facilitate further understanding and implementation of ESP in higher education. Future study should inquire the efficiency of this innovation. Keywords: ESP education, AEC of 2015, curriculum, competition, communication.